White Evangelical Racism: The Politics of Morality in America - Butler, Anthea D. (A Ferris and Ferris Book Ser., 2021)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Introduction: Evangelical Racism: A Feature, Not a Bug -- 1. The Racist Foundations of Evangelicalism in the Nineteenth Century -- 2. Saving the Nation: Fervor, Fear, and Challenges to Jim Crow -- 3. Whitewashing Racism and the Rise of the Religious Right -- 4. How Firm a Foundation: A Twenty-First-Century Precipice Appears -- Conclusion: Whom Will You Serve? -- Acknowledgments -- Selected Reading -- Index -- A -- B -- C -- D -- E -- F -- H -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y.